1997
DOI: 10.1021/jf960810n
|View full text |Cite
|
Sign up to set email alerts
|

4-Substituted Resorcinols (Sulfite Alternatives) as Slow-Binding Inhibitors of Tyrosinase Catecholase Activity

Abstract: A kinetic study of the inhibition of mushroom tyrosinase catecholase activity by 4-substituted resorcinols has been made. The results obtained show that 4-substituted resorcinols inhibit tyrosinase in a nonclassical manner and that the inhibition is characterized by a long transient phase. Progress curves of enzymatic reaction in the presence of inhibitor show a progressive decrease in initial velocity followed by a constant steady-state rate. Both the initial and the constant rates decreased with increasing c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
2
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(42 citation statements)
references
References 21 publications
2
37
2
1
Order By: Relevance
“…23) Among linear-chain orsellinates, inhibitory activity rose with increasing number of carbons in the alkyl chain-namely, n-butyl (90.59%)<n-pentyl (65.92%)<n-hexyl (58.55%)<n-octyl orsellinate (45.62%)-corroborating the findings of Huang et al, 13) who observed that the inhibitory properties of p-alkyl benzoic acids were potentiated by increasing the length of hydrocarbon chains. A similar result was obtained by Jiménez et al, 9) who found 4-hexylresorcinol to be more active than 4-ethylresorcinol in preventing L-3,4-dihydroxyphenylalanine (L-DOPA) oxidation to DOPA-quinone. However, the enhancement of tyrosinase activity with increasing length of hydrocarbon chains is expected to peak at a linear alkyl chain of eight to ten carbons.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…23) Among linear-chain orsellinates, inhibitory activity rose with increasing number of carbons in the alkyl chain-namely, n-butyl (90.59%)<n-pentyl (65.92%)<n-hexyl (58.55%)<n-octyl orsellinate (45.62%)-corroborating the findings of Huang et al, 13) who observed that the inhibitory properties of p-alkyl benzoic acids were potentiated by increasing the length of hydrocarbon chains. A similar result was obtained by Jiménez et al, 9) who found 4-hexylresorcinol to be more active than 4-ethylresorcinol in preventing L-3,4-dihydroxyphenylalanine (L-DOPA) oxidation to DOPA-quinone. However, the enhancement of tyrosinase activity with increasing length of hydrocarbon chains is expected to peak at a linear alkyl chain of eight to ten carbons.…”
Section: Resultssupporting
confidence: 83%
“…7) Tyrosinase inhibitors are often structurally analogous to phenolic substrates, which generally show competitive inhibition. A number of naturally occurring tyrosinase inhibitors have been described, mostly phenols and polyphenols, 8) resorcinol derivatives, [9][10][11] benzoic acid and pyridine derivatives, 12,13) gallate derivatives, 14) and vanillin derivatives. 15) However, only a few compounds are known to serve as effective tyrosinase inhibitors, owing to high toxicity, low activity, or economic factors.…”
mentioning
confidence: 99%
“…However, the ability of artocarpanone to reduce melanin biosynthesis in mushroom tyrosinase assay may be related to the presence of a 4-substituted resorcinol moiety in its chemical structure. As suggested by Shimizu et al, 24) Jimenez and Garcia-Carmona, 25) and Chen et al, 26) a 4-substituted resorcinol moiety inhibits tyrosinase activity. The mechanism of inhibition of melanin production in B16 melanoma cells by artocarpanone is still unclear, but although we believe that a 4-substituted resorcinol moiety may be related to the inhibitory activity.…”
Section: Discussionmentioning
confidence: 81%
“…The equilibria between enzyme, inhibitor and enzyme-inhibitor complexes occur slowly in the steady-state time scale. Other slow-binding inhibition of tyrosinases from different sources (frog epidermis and mushroom) by several inhibitors (m-coumaric acid, L-mimosine and 4-substituted resorcinols) has also been reported [144][145][146]. 4-Substituted resorcinols, which are structurally related to phenolic substrates such as other slow-binding inhibitors, have recently been recognized as tyrosinase inhibitors.…”
Section: Inhibitors From Synthetic Originsmentioning
confidence: 99%
“…4-Hexylresorcinol is claimed to be the most effective inhibitor for use in the food industry since it is water soluble, stable, nontoxic, nonmutagenic and noncarcinogenic, and it has been recognized as safe for use in the prevention of shrimp melanosis and for browning control of fresh and hot-air-dried apple slices as well as potatoes and avocados [148,149]. In the kinetic study, progress curves of enzymatic reaction in the presence of 4-substituted resorcinols showed a progressive decrease in initial velocity followed by a constant steady-state rate [146]. Both the initial and the constant rates decreased with increasing concentrations of the inhibitor.…”
Section: Inhibitors From Synthetic Originsmentioning
confidence: 99%